IMPROVING STUDENTS’ READING SKILL THROUGH THE REPORT TEXTS - Sitoresmi, Woro Endah; Alicia, Velma (ASOSIASI IDEBAHASA KEPRI, 2024)
Reading is one of fundamental skills that must be owned by the learners to master English language. In comprehending the content of the text, reading is a key to have it. However, to own good reading skill in English language is not an easy matter. There are several ways to be paid attention by the learners namely decoding knowledge, vocabularies and the use of grammar. In addition, reading does not only become one of English skills but broadly it is the real way to make the students more knowledgeable through the Report texts. This program involves three activities such as pre-reading activities, reading activities, and post-reading activities. The goals of this project are basically to encourage the learners for having reading habit, to increase the vocabularies and specifically to create students’ critical thinking. This project takes place in SMP Islam Plus Baitul Maal, Pondok Aren, Kota Tangerang Selatan.